Analisis Penggunaan Software Akuntansi Spredsheet Terhadap Ketepatan Pencatatan Penjualan dan Penyajian Laporan Keuangan Pada PT. Indomaret Cabang Bogor 2 - Sepiya Febiola; Dessy Evianti (Jurnal Informatika Kesatuan, 2021)
The use of accounting software in a company plays an important role in obtaining financial information because the use of appropriate accounting software can help time effectiveness in managing data and minimizing errors so that companies can make decisions appropriately and quickly from the financial information obtained. The research object is PT. Indomaret Bogor Branch 2, is a retail company that sells products such as food and daily equipment as well as serving transaction services such as ticket payments, electricity and water bills as well as serving online transaction payments which are located at Jl Raya Bogor Km 46.7 Kel. Nanggewer Mekar Kec. Cibinong, Bogor Regency. The purpose of this study is to find out how the use of spreadsheet software for the accuracy of sales records and financial reports at PT.Indomaret Bogor Branch 2 and to find out how to implement the use of accurate accounting software at PT. Indomaret Bogor Branch 2. Data obtained through interviews and observations. The results showed that the use of spreadsheet accounting software at PT.Indomaret Bogor 2 branch had quite a lot of shortcomings. Transactions that are inputted are only sales and are quite risky for human error in data entry. The resulting financial statements are manual using Microsoft Excel including recording in cash & bank transactions. The implementation of the use of aaccounting software accurate runs well, data input is faster and integrated starting from the purchase, sale, fixed assets, cash & bank modules and the resulting financial reports, human errors can be minimized. The quality of the information generated can be better and updated. Keywords: Accounting Information Systems, Spreadsheet Accounting Software, Accurate Accounting Software, Sales, Financial Statements.